The complete mitochondrial genome sequence and phylogenetic analysis of Squalidus multimaculatus. Issue 3 (2nd July 2020) - Park, So Young; Kim, Sang Ki; Sagong, Jin; Ryu, Shi-Hyun; Yu, Jeong-Nam
Abstract: This study reports the complete mitochondrial genome of Squalidus multimaculatus . The length of the mitochondrial genome of S. multimaculatus is 16, 597 bp, including 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and one control region. The overall base composition of A, G, T, and C is 28%, 18.8%, 25%, and 28.2%, respectively. A phylogenetic analysis by the neighbour-joining method showed a close relationship between S. multimaculatus and S. japonicus coreanus . We believe these results will provide essential data for phylogeographic studies of the genus Squalidus .